2021
DOI: 10.3390/cells10113247
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Exosomal PD-L1 in Cancer Progression and Its Potential as a Therapeutic Target

Abstract: Binding of programmed cell death ligand 1 (PD-L1) to its receptor programmed cell death protein 1 (PD-1) can lead to the inactivation of cytotoxic T lymphocytes, which is one of the mechanisms for immune escape of tumors. Immunotherapy based on this mechanism has been applied in clinic with some remaining issues such as drug resistance. Exosomal PD-L1 derived from tumor cells is considered to play a key role in mediating drug resistance. Here, the effects of various tumor-derived exosomes and tumor-derived exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…PD-L1 is an immunosuppressive ligand associated with immune evasion in cancer [ 27 ]. Multiple studies demonstrated elevated sEV PD-L1 levels in different cancer entities, which correlated with poor patient prognosis [ 28 , 29 ]. Moreover, Theodoraki et al observed that low sEV PD-L1 content is linked to shorter disease-free survival in HNC cancer and, thus, an unfavorable prognostic factor [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is an immunosuppressive ligand associated with immune evasion in cancer [ 27 ]. Multiple studies demonstrated elevated sEV PD-L1 levels in different cancer entities, which correlated with poor patient prognosis [ 28 , 29 ]. Moreover, Theodoraki et al observed that low sEV PD-L1 content is linked to shorter disease-free survival in HNC cancer and, thus, an unfavorable prognostic factor [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Without being internalized, TEX may deliver their surface ligands to T cell surface receptors to modulate gene expression and functions of T cells [164]. Binding of programmed cell death ligand 1 (PD-L1) to its receptor, programmed cell death protein 1 (PD-1), can lead to the inactivation of cytotoxic T lymphocytes, which is one of the mechanisms for immune escape of tumors [165]. Chen et al reported that TEX released by metastatic melanomas carry PD-L1 on their surface, which suppressed the function of CD8 + T cells and facilitated tumor growth [3].…”
Section: Via Surface Ligandmentioning
confidence: 99%
“…When it comes to the lymphatic level, exoPD-L1 will inhibit the production of memory T cells, favoring lymphatic tumor spread. ExoPD-L1 plasma release has also been proved to be responsible for distant immunosuppression [ 22 , 23 ].…”
Section: Soluble and Exosomal Pd-l1mentioning
confidence: 99%
“…In addition to its immunosuppressive role, the most recent evidence places exoPD-L1 as one of the mechanisms of resistance to anti-PD-L1/PD-1 therapy [ 23 ]. Preclinical studies and phase I clinical trials have shown an association between the baseline levels of exoPD-L1 and a low response rate to treatment with ICI in NSCLC, metastatic melanoma, and head and neck tumors [ 21 , 22 , 23 , 24 ].…”
Section: Soluble and Exosomal Pd-l1mentioning
confidence: 99%